Imaging features, clinical characteristics and neonatal outcomes of pregnancy luteoma: A case series and literature review - Jian‐Hong Shang; Cai‐Xin Huang; Qiao Zheng; Jie‐Ling Feng; Ke He; Hong‐Ning Xie (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction This study aimed to investigate the imaging features, clinical characteristics and neonatal outcomes of pregnancy luteoma. Material and methods We retrospectively analyzed patients with pregnancy luteoma admitted to the First Affiliated Hospital of Sun Yat‐sen University between January 2003 and December 2022. We recorded their imaging features, clinical characteristics and neonatal outcomes. Additionally, we reviewed relevant studies in the field. Results In total, 127 cases were identified, including eight from our hospital and 119 from the literature. Most patients (93/127, 73.23%) were of reproductive age, 20–40 years old, and 66% were parous. Maternal hirsutism or virilization (such as deepening voice, acne, facial hair growth and clitoromegaly) was observed in 29.92% (38/127), whereas 59.06% of patients (75/127) were asymptomatic. Abdominal pain was reported in 13 patients due to compression, torsion or combined ectopic pregnancy. The pregnancy luteomas, primarily discovered during the third trimester (79/106, 74.53%), varied in size ranging from 10 mm to 20 cm in diameter. Seventy‐five cases were incidentally detected during cesarean section or postpartum tubal ligation, and 39 were identified through imaging or physical examination during pregnancy. Approximately 26.61% of patients had bilateral lesions. The majority of pregnancy luteomas were solid and well‐defined (94/107, 87.85%), with 43.06% (31/72) displaying multiple solid and well‐circumscribed nodules. Elevated serum androgen levels (reaching values between 1.24 and 1529 times greater than normal values for term gestation) were observed in patients with hirsutism or virilization, with a larger lesion diameter (P < 0.001) and a higher prevalence of bilateral lesions (P < 0.001). Among the female infants born to masculinized mothers, 68.18% (15/22) were virilized. Information of imaging features was complete in 22 cases. Ultrasonography revealed well‐demarcated hypoechoic solid masses with rich blood supply in 12 of 19 cases (63.16%). Nine patients underwent magnetic resonance imaging (MRI) or computed tomography (CT), and six exhibited solid masses, including three with multi‐nodular solid masses. Conclusions Pregnancy luteomas mainly manifest as well‐defined, hypoechoic and hypervascular solid masses. MRI and CT are superior to ultrasonography in displaying the imaging features of multiple nodules. Maternal masculinization and solid masses with multiple nodules on imaging may help diagnose this rare disease.